Regenerative futures: a transformation of Upphärad beyond sustainability - Karlkvist, Katarina; Nyman, Josefin (My University, 2022)
To meet the current climate crisis and the problematic effects of the urban norm society needs to shift. It needs to go from the growth paradigm to a paradigm of regenerative development to reach a future beyond sustainability. The thesis aims to through a local situation exemplify how society on a larger scale can accomplish shifting towards a future beyond sustainability. This is done using three focus perspectives in the rural context of Upphärad. The three focuses are reducing greenhouse gas emissions, circular systems, and regenerative design. Several methods, such as literature reviews and dialogues with professionals, are combined through research for design and research by design in an iterative process. The theoretical framework covers the discourses of the growth paradigm, the urban norm, as well as how a future beyond sustainability can develop in relation to the three focuses. A design proposal is generated by combining top-down and bottom-up information. The design proposal is directed at the local scale of Upphärad. It is “urban” design of a rural environment, but also planning of society, as it imagines a future scenario beyond sustainability. The thesis also draws conclusions about society on a larger level, discussing how local bottom-up initiatives can be supported by collaborations with top-down actors. In rural contexts the bottom-up initiatives are essential for the development beyond sustainability. The thesis discusses how the physical environment should be flexible and adaptable over time to meet changing needs of the community. Further, the physical environment should gather multiple functions close to each other to facilitate synergies that can create added values. The community needs facilities that support creation of values outside of the growth paradigm and the urban norm. The thesis also draws conclusions regarding the need to be more locally self-sufficient, as this feeds into many of the strategies necessary for a societal shift beyond sustainability. Additionally, the thesis result functions as inspirational material and generates a basis for discussion regarding a societal shift to regenerative futures beyond sustainability.
Keywords: Beyond sustainability, Reducing GHG emissions, Circular system, Regenerative design, Rurban context